Structural features and antioxidant activities of polysaccharides from different parts of Codonopsis pilosula var. modesta (Nannf.) L. T. Shen - Li, Li-Xia; Chen, Meng-Si; Zhang, Zi-Yu; Paulsen, Berit Smestad; Rise, Frode; Huang, Chao; Feng, Bin; Chen, Xing-Fu; Jia, Ren-Yong; Ding, Chun-Bang; Feng, Shi-Ling; Li, Yang-Ping; et al. (Frontiers in Pharmacology, 2022)
In this study, three acidic polysaccharides from the different plant parts of Codonopsis pilosula var. modesta (Nannf.) L. T. Shen were obtained by ion exchange chromatography and gel filtration chromatography. Compared with polysaccharides from roots (CLRP-1) and aerial parts (CLSP-1), polysaccharides from rhizomes and fibrous roots (CLFP-1) had the lowest antioxidant activity, so CLRP-1 and CLSP-1 were used for structural elucidation and anti-oxidant activity studies. The molecular weight of CLRP-1 was 15.9 kDa and CLSP-1 was 26.4 kDa and the monosaccharide composition of two polysaccharides were Ara, Rha, Fuc, Xyl, Man, Gal, GlcA, GalA in a ratio of 3.8: 8.4: 1.0: 0.8: 2.4: 7.4: 7.5: 2.0: 66.7 in CLRP-1 and Ara, Rha, Gal, GalA in a ratio of 5.8: 8.9: 8.0: 77.0 in CLSP-1. CLRP-1 and CLSP-1 consisted of 12 structural residues. The results of structure elucidation indicated that both CLRP-1 and CLSP-1 were pectic polysaccharides, mainly composed of 1, 4-linked galacturonic acid with long homogalacturonan regions. Arabinogalactan type I and arabinogalactan type II were presented as side chains. The antioxidant assay in IPEC-J2 cells showed that both CLRP-1 and CLSP-1 promoted cell viability and antioxidant activity, which significantly increase the level of total antioxidant capacity and the activity of superoxide dismutase, catalase, and decrease the content of malondialdehyde. Moreover, CLRP-1 and CLSP-1 also showed powerful antioxidant abilities in Caenorhabditis elegans and might regulate the nuclear localization of DAF-16 transcription factor, induced antioxidant enzymes activities, and further reduced reactive oxygen species and malondialdehyde contents to increase the antioxidant ability of Caenorhabditis elegans. Thus, CLRP-1 and CLSP-1 could be used as potential antioxidants.